Executive Function and Self-Regulation: Bi-Directional Longitudinal Associations and Prediction of Early Academic Skills - Howard, Steven J.; Vasseleu, Elena; Neilsen-Hewett, Cathrine; de Rosnay, Marc; Chan, Amy Y. C.; Johnstone, Stuart; Mavilidi, Myrto; Paas, Fred; Melhuish, Edward C. (Frontiers in Psychology, 2021)
Despite a tendency to study executive function (EF) and self-regulation (SR) separately, parallel lines of research suggest considerable overlap between the two abilities. Specifically, both show similar developmental trajectories (i.e., develop rapidly in the early years), predict a broad range of overlapping outcomes across the lifespan (e.g., academic success, mental and physical health, social competence), and have overlapping neural substrates (e.g., prefrontal cortex). While theoretical frameworks diverge in how they reconcile EF and SR – ranging from treating the two as functionally synonymous, to viewing them as related yet distinct abilities – there is no consensus and limited empirical evidence on the nature of their relationship and how this extends developmentally. The current study examined bi-directional longitudinal associations between early EF and SR, and their longitudinal associations with subsequent early academic skills, in a sample of 199 3- to 5-year-old pre-school children. The adopted measures permitted EF and SR to be modelled as composite indices for these analyses, thereby decreasing task-specific components of these associations. Early academic skills were captured by a standardized direct assessment. Bi-directional associations between EF and SR were found, with both accounting for unique variance in early academic skills 7 and 19 months later. The current results provide important evidence to distinguish between EF and SR abilities, yet also for their reciprocal influence in-situ and across early development.